Analisis Pemahaman Budaya Kerja bagi Calon Tenaga Kerja Migran Ke Jepang di LPK Wisma Berkah Sejahtera - Umi Handayani; Hendrike Priventa; Rosalina Wahyu Riani; Ahmad Sarif Nurul Arifin; Adilla Wira Wati (Vocational College of Diponegoro University, 2026)
This study aims to analyze the understanding of Japanese work culture among prospective Indonesian migrant workers to Japan who participate in training programs at LPK Wisma Berkah Sejahtera. The focus of the study includes the forms of work culture training provided, the participants’ level of understanding of Japanese work culture values, and the factors that hinder the process of cultural understanding. This research employs a mixed-methods approach, combining qualitative and quantitative methods. Qualitative data were obtained through structured non-participant observation and in-depth interviews with instructors and training participants, while quantitative data were collected through a Likert-scale questionnaire measuring five indicators of Japanese work culture: work discipline, teamwork and communication, politeness and respect, honesty and responsibility, and hard work and dedication. The results indicate that LPK Wisma Berkah Sejahtera has implemented Japanese work culture training in a relatively comprehensive manner through chorei activities, integrated Japanese language learning, interview training (mensetsu), dedicated Japanese culture classes, and interpersonal skills training. The participants’ level of understanding ranges from moderate to good, with the highest levels observed in the aspects of honesty and responsibility, politeness and respect, and teamwork and communication. However, gaps in general understanding of Japanese work culture remain, along with several obstacles, including the predominance of theoretical training materials, language barriers, differences in communication styles, mental and physical preparedness, and limited instructor resources.